Dialek-dialek Melayu di Lembah Baram - Chong Shin, (Universiti Kebangsaan Malaysia, 2009)
This paper attempt to study the Malay dialects spoke in Baram River, Northern Sarawak. Three Malay dialects have been revealed in this area, namely (1) the Sarawak Malay Dialect (SMD) (2) Brunei Malay Dialect (BMD); and (3) Baram Malay (BM). Linguistically, the SMD in Baram river basin is identified as a subvariant of SMD in Sarawak (similar to the Rejang, Saribas and Kuching dialect). The SMD, which only consists of three vowels, is categorized as the sub dialect of Brunei Malay. This paper also described the BM studied by Needham (1958). In brief, BM is a kind of Bazaar Malay which is widely spoken by the non-Malay tribes in Baram river basin